Interconnecting Land Registers at the European Level: Technological Progress and Harmonization Aspects - Gołaczyński, Jacek; Kaczorowska, Maria (Review of European and Comparative Law, 2023)
Characterized by a substantial diversity and falling within the property law domain, land registration systems have been excluded from the European Union harmonization process. At the same time, however, cross-border access to land registry information is critical for the development of the internal market. Therefore, several ambitious strategies are being pursued at the European level to interconnect national land registers by fully exploiting the possibilities offered by the latest technological advances. This article investigates the effect of transnational cooperation initiatives aimed at interconnecting electronic land registers within the European e-Justice program for the enhancement of the integration of the real estate markets in Member States. In this respect, legal challenges connected with the standardization of land information are addressed from comparative and harmonization perspectives.